Efl Students' Critical Thinking in Speaking Activities - Rahmat Maulana; Muhammad Iqbal Ripo Putra; Finny Anita (Jurnal Pendidikan Bahasa, 2022)
This research aimed to investigate how EFL students apply critical thinking in speaking activities and to explore the levels of critical thinking achieved by EFL students in speaking activities at e-COLINK Pontianak. The population of this research was the EFL students of advanced level 3 at e-COLINK Pontianak with a total of eight students. The samples of this research were selected using total sampling technique. The researcher applied the type of descriptive research with a qualitative approach. The techniques of data collection used in this research were observation and direct communication. For collecting the data, the researcher used the instruments such as field notes and interview. To analyze the data, the researcher used descriptive qualitative analysis, which was based on the theory from Ary, Jacobs, Sorensen, Walker (2014). As the results, the researcher revealed that the EFL students applied critical thinking in speaking activities based on the indicators of critical thinking from some authors that had been summarized into six sections. The levels of critical thinking achieved by the EFL students were level of Understand and Apply which indicated as low level, and level of Evaluate which indicated as high level.